EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR DALAM PEMBELAJARAN MENULIS KARANGAN PERSUASI DI KELAS VIII.D SMP NEGERI 2 LENGAYANG KABUPATEN PESISIR SELATAN - Listianda, Rifera; Nursaid, Nursaid; Ramadansyah, Ramadansyah (Pendidikan Bahasa Indonesia, 2013)
The background of this research problem was lack of ability to write a persuasive essay in class VIII.D junior high school Number 2 Lengayang Pesisir Selatan District. Low interest of students in writing essays of persuasion due to the method used is the lecture method resulting in saturated and bored students on the material being taught, so that the necessary techniques that are able to improve essay writing skills of persuasion. This study aimed to describe the comparison of the ability to write persuasive essays before and after the use of media images in teaching writing persuasive essay in class VIII.D junior high school Number 2 Lengayang Pesisir Selatan District.            This research is quantitative research. The technique used in this study are pre with the research  design of pre - test and post -test. The population in this study is the eighth grade students of SMP Negeri 2 Lengayang Pesisir selatan  district listed in 2012/2013 which consists of 7 classes. collect the sample is purposive sampling and the sample is grade VIII.D.the instrument use of the test about performance of writing a persuasive essay. techniques  to collect the data is done in two stages, before and after using the media image.            Based on the results of a study of the ability to write persuasive essays before and after the use of media images can conclude the following points. First , the ability to write persuasive essays before using media images eighth grade students of junior high school number 2 Lengayang Pesisir Selatan District are at nearly qualified enough ( HC ) with an average value of 52.86. Second, the ability to write persuasive essays after using media images eighth grade junior high student 2 Lengayang Pesisir selatan District are in good qualification ( B ) with an average value of 75.93. Third, there are significant differences from before and after the use of media to use images in teaching media writing persuasive essays of t-test results at the level of 0.05 t = 12.8 > t table = 1.70 thus H1 is accepted. Student learning outcomes in persuasion fabricated using media images more effectively.